2009
DOI: 10.11646/zootaxa.2106.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Geothelphusa makatao sp. nov. (Crustacea: Brachyura: Potamidae), a new freshwater crab from an uplifted Pleistocene reef in Taiwan

Abstract: A new species of potamid freshwater crab, Geothelphusa makatao, is described from southwestern Taiwan, based on morphological characters and mitochondrial DNA evidence. The new species differs from close congeners, G. pingtung Tan & Liu, 1998, G. shernshan Chen, Cheng & Shy, 2005, and G. ancylophallus Shy, Ng & Yu, 1994 and a superficially similar species, G. albogilva Shy, Ng & Yu, 1994, in the structure of its ambulatory legs, thoracic sternum, male abdomen, and male first pleopods. The uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As overlapping ranges between species are rare, we can attribute the philopatry of freshwater crabs to enclosed drainage systems, as shown previously (e.g. Daniels, ; Shih et al ., ; Jesse et al ., , ). Thus, in freshwater crabs allopatry is an important factor in the evolution and maintenance of species boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As overlapping ranges between species are rare, we can attribute the philopatry of freshwater crabs to enclosed drainage systems, as shown previously (e.g. Daniels, ; Shih et al ., ; Jesse et al ., , ). Thus, in freshwater crabs allopatry is an important factor in the evolution and maintenance of species boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Ng, ; Ng & Chia, ; Cumberlidge & Ng, ), and freshwater crab distributions in general have been shown to reflect palaeogeography (e.g. Daniels et al ., ; Shih et al ., ; Klaus et al ., ; Jesse et al ., ). Two families of primary freshwater crabs occur in Southeast Asia: the Potamidae and the Gecarcinucidae.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mitochondrial markers, large subunit (16S) ribosomal (r)RNA and cytochrome oxidase I (COI), have proven to be useful markers for suggesting species boundaries and phylogeny of crabs and shrimps (e.g., Schubart et al, 2000;Chu et al, 2003;Shih et al, 2004Shih et al, , 2006Shih & Cai, 2007;Shih & Suzuki, 2008;Shih & Shy, 2009). However for Uca, the only attempt at a genetically based phylogeny has been the joint study using 16S rRNA reported by Levinton et al (1996) and Sturmbauer et al (1996).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Geothelphusa , nearly 40 species have been described from Taiwan, many of them recently ( Shih and Ng 2011 ; Shy et al 2014 , 2020 , 2021 ), and new species descriptions are still underway (cf. Shy et al 2020 ), although a few of them have been synonymized ( Shih and Shy 2009 ; Shih and Ng 2011 ; Shy et al 2020 , 2021 ) or at least suggested to be conspecific ( Shih et al 2023 ). In contrast, Candidiopotamon has only one described species in Taiwan, i.e., Candidiopotamon rathbuni (De Man, 1914), occurring throughout the island.…”
Section: Introductionmentioning
confidence: 99%